Cold non‐ischemic heart preservation with continuous perfusion prevents early graft failure in orthotopic pig‐to‐baboon xenotransplantation. (25th August 2020) - Längin, Matthias; Reichart, Bruno; Steen, Stig; Sjöberg, Trygve; Paskevicius, Audrius; Liao, Qiuming; Qin, Guangqi; Mokelke, Maren; Mayr, Tanja; Radan, Julia; Issl, Lara; Buttgereit, Ines; et al.
Abstract: Background: Successful preclinical transplantations of porcine hearts into baboon recipients are required before commencing clinical trials. Despite years of research, over half of the orthotopic cardiac xenografts were lost during the first 48 hours after transplantation, primarily caused by perioperative cardiac xenograft dysfunction (PCXD). To decrease the rate of PCXD, we adopted a preservation technique of cold non‐ischemic perfusion for our ongoing pig‐to‐baboon cardiac xenotransplantation project. Methods: Fourteen orthotopic cardiac xenotransplantation experiments were carried out with genetically modified juvenile pigs (GGTA1‐ KO/hCD46/hTBM) as donors and captive‐bred baboons as recipients. Organ preservation was compared according to the two techniques applied: cold static ischemic cardioplegia (IC; n = 5) and cold non‐ischemic continuous perfusion (CP; n = 9) with an oxygenated albumin‐containing hyperoncotic cardioplegic solution containing nutrients, erythrocytes and hormones. Prior to surgery, we measured serum levels of preformed anti‐non‐Gal‐antibodies. During surgery, hemodynamic parameters were monitored with transpulmonary thermodilution. Central venous blood gas analyses were taken at regular intervals to estimate oxygen extraction, as well as lactate production. After surgery, we measured troponine T and serum parameters of the recipient's kidney, liver and coagulation functions. Results: In porcine grafts preserved with IC, we found significantly depressed systolic cardiac function after transplantation which did not recover despite increasing inotropic support. Postoperative oxygen extraction and lactate production were significantly increased. Troponin T, creatinine, aspartate aminotransferase levels were pathologically high, whereas prothrombin ratios were abnormally low. In three of five IC experiments, PCXD developed within 24 hours. By contrast, all nine hearts preserved with CP retained fully preserved systolic function, none showed any signs of PCXD. Oxygen extraction was within normal ranges; serum lactate as well as parameters of organ functions were only mildly elevated. Preformed anti‐non‐Gal‐antibodies were similar in recipients receiving grafts from either IC or CP preservation. Conclusions: While standard ischemic cardioplegia solutions have been used with great success in human allotransplantation over many years, our data indicate that they are insufficient for preservation of porcine hearts transplanted into baboons: Ischemic storage caused severe impairment of cardiac function and decreased tissue oxygen supply, leading to multi‐organ failure in more than half of the xenotransplantation experiments. In contrast, cold non‐ischemic heart preservation with continuous perfusion reliably prevented early graft failure. Consistent survival in the perioperative phase is a prerequisite for preclinical long‐term results after cardiac xenotransplantation.